Is it the injection device or the anxiety experienced that causes pain during dental local anaesthesia? - OZGUR ONDER KUSCU & SERAP AKYUZ (IAPD and Blackwell, 2008)
Pain is a highly complex and multidimensional phenomenon that energizes the organism, regardless of real or apparent tissue damage, to take action in relieving or alleviating its presence 1 . It is important to acknowledge that the pain sensation is not necessarily dependent on tissue damage; it may also be generated by conditioned stimuli such as the sound of the drill or a gentle touch of the needle during local anaesthetic injections